Nature readers - Wright, Julia McNair, 1840-1903; King, C. S. (Salt Lake City, UT : Project Gutenberg, 2023)
"Nature Readers: Sea-side and Way-side. No. 3" by Julia McNair Wright is a children's educational series written in the late 19th century. This installment appears to focus on nature, particularly emphasizing the role of the earth, plants, and the relationships they have with animals and humans. The work aims to present knowledge in an engaging and enjoyable manner, encouraging children to appreciate and explore the natural world around them. The opening of the book introduces the author$1 (Bs intent and the overarching theme of the series. Julia McNair Wright expresses her desire to cultivate an appreciation for nature among children, guiding them through lessons about earth$1 (Bs flora and fauna while making the content accessible and fun. The first lesson titled "The Great Mother" highlights the importance of the earth and its resources, exploring the interconnectedness of living beings and their reliance on plants for food, shelter, and various needs. Through conversations between children, she illustrates the value of the soil, emphasizing that all life stems from it, setting the stage for deeper explorations of plant life and natural phenomena in the subsequent lessons. (This is an automatically generated summary.)s
No. 3 has chapters on plant-life, grasshoppers, butterflies, and birds.
Release date is 2023-11-05
Carla Foust and The Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Readers; Nature study -- Juvenile literature